A note on four nonradioactive labeling systems for dot hybridization detection of potato viruses - Audy, P.; Parent, J.-G.; Asselin, A. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1991)
Complementary DNA clones of genomic RNAs of potato (Solarium tuberosum) viruses S (PVS), X (PVX) and Y (PVY) were produced and tested for their capacity to hybridize with various plant virus RNAs. PVS clone S12 and PVX clone X6 were found to be very specifie to PVS and PVX RNA respectively, whereas PVY clone Y10 strongly hybridized with PVY RNA and weakly with PVS RNA. Four commercial, nonradioactive Systems of nucleic acid labeling and detection were compared to the usual 32P-labeled probe using dot hybridization experiments. Colorimetric detection of digoxigenin-labeled DNA probes gave a level of sensitivity of 1 ng of virions (60 pg of RNA), similar to autoradiography of 32P-labeled probes. Sulfonated, biotinylated and peroxidase-labeled probes were slightly less sensitive, allowing detection of 600 pg of viral RNA.